Utilisation, Availability and Price Changes of Medicines and Protection Equipment for COVID-19 Among Selected Regions in India: Findings and Implications - Haque, Mainul; Kumar, Santosh; Charan, Jaykaran; Bhatt, Rohan; Islam, Salequl; Dutta, Siddhartha; Abhayanand, Jha Pallavi; Sharma, Yesh; Sefah, Israel; Kurdi, Amanj; Wale, Janney; Godman, Brian (Frontiers in Pharmacology, 2021)
Background: COVID-19 has already claimed a considerable number of lives worldwide. However, there are concerns with treatment recommendations given the extent of conflicting results with suggested treatments and misinformation, some of which has resulted in increased prices and shortages alongside increasing use and prices of personal protective equipment (PPE). This is a concern in countries such as India where there have been high patient co-payments and an appreciable number of families going into poverty when members become ill. Community pharmacists do play a significant role in disease management in India, and this will remain. Consequently, there is a need to review prices and availability of pertinent medicines during the current COVID-19 pandemic. Objective: Assess current utilisation and price changes as well as shortages of pertinent medicines and equipment during the pandemic and the implications. Our Approach: Multiple approach involving a review of treatments and ongoing activities in India to reduce the spread of the virus alongside a questionnaire among pharmacies from early March to end May 2020. Our activities: 111 pharmacies took part, giving a response rate of 80%. Encouragingly, no change in utilisation of antimalarial medicines in 45% of pharmacies despite endorsements and for antibiotics in 57.7% of pharmacies, helped by increasing need for a prescription. In addition, increased purchasing of PPE (over 98%). No price increases were seen for antimalarials and antibiotics in 83.8% and 91.9% of pharmacies respectively although shortages were seen for antimalarials in 70.3% of pharmacies, lower for antibiotics (9.9% of pharmacies). However, price increases were typically seen for PPE (over 90% of stores) as well as for analgesics (over 50% of pharmacies). Shortages were also seen for PPE (88.3%). Conclusion: The pandemic has impacted on utilisation and prices of pertinent medicines and PPE in India but moderated by increased scrutiny. Key stakeholder groups can play a role with enhancing evidenced-based approaches and reducing inappropriate purchasing in the future.